Lactate Metabolism and Lactylation Modification: New Opportunities and Challenges in Cardiovascular Disease - Mengyang Song; Bin Liu; Haiou Wang; Wei Sun (MedComm, 2025)
ABSTRACT Traditionally regarded as a metabolic waste product, lactic acid is now recognized as a crucial molecule in energy metabolism and signal transduction. It regulates various biological processes, including intracellular inflammation and immune responses. Notably, a novel epigenetic modification, lactylation, which is directly linked to lactic acid, was first identified by Professor Zhao Yingming's team in 2019. Lactylation influences gene expression and is associated with inflammation, cancer, and ischemic disease. Despite its potential significance, the precise mechanisms by which lactylation regulates gene expression remain unclear, and its implications in cardiovascular diseases are not yet fully understood. This review elucidates the relationship between lactic acid metabolism and cellular functions, highlighting its significant biological roles. This review provides a comprehensive analysis of the mechanistic role of lactylation in disease progression. It synthesizes research findings and emerging trends concerning lactic acid production and lactylation in the context of cardiovascular diseases. We explored potential therapeutic agents targeting lactylation and identified prospective treatment targets, offering novel insights into and directions for intervention strategies related to lactic acid production and lactylation. Ultimately, this review aims to pave the way for new therapeutic and research avenues in cardiovascular diseases.